An experimental investigation on physical‐mechanical‐tribological performance of thermoplastic composites with partial sand replacements. Issue 9 (13th September 2022) - Soni, A.; Das, P.K.; Yusuf, M.
Abstract: Growing population, industrialization, urbanization, etc. are the consequences of increasing plastic waste, which is deteriorating the environment's health. The study explores the potential of waste plastics as a value‐added material. The composite samples of floor tiles were developed using 50 wt. %, 60 wt. %, 70 wt. % and 100 wt. % of low‐density polyethylene and sand. The developed samples were evaluated for water absorption, compressive strength, flexural strength, sliding wear, and friction coefficient. The water absorption decreases gradually with replacements. The ranges for compressive and flexural strength were found to be 37.24×10 −6  N/m 2 to 46.20×10 −6  N/m 2 and 4.81×10 −6  N/m 2 to 6.24×10 −6  N/m 2 respectively having maximum values of 46.20×10 −6  N/m 2 and 6.24×10 −6  N/m 2 respectively, for 50 wt. % of low‐ density polyethylene. The incorporation of sand improves the wear performance at moderate to high loads. The friction coefficient depends on load and surface asperities. The structural analysis showed that the fillers are completely encapsulated and mechanically bonded into the matrix. The morphological analysis of the surfaces correlates the fracture mechanism with the properties of the composites. Abstract : The research explores the potential of waste plastic and sand as thermoplastic composites. The research aims to study the effects of the replacement of plastic on the characteristics of the developed composites. The structural and morphological analysis correlates the fracture mechanisms with the properties of the composites.